2016
DOI: 10.1016/j.yebeh.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for spared attention to faces in 7-month-old infants after prenatal exposure to antiepileptic drugs

Abstract: a b s t r a c t a r t i c l e i n f oIntroduction: Prenatal antiepileptic drug (AED) exposure is associated with an increased risk of cognitive impairment and autism spectrum disorders detected mainly at the age of two to six years. We examined whether the developmental aberrations associated with prenatal AED exposure could be detected already in infancy and whether effects on visual attention can be observed at this early age. Material and methods: We compared a prospective cohort of infants with in utero ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…In a recent study by Videman et al, carbamazepine, oxcarbazepine, and VPA were associated with impaired early language abilities at the age of 7 months. In contrast, face perception or social attention may be less affected by the neurotoxic effects of the studied AEDs [50]. Previously, the association between prenatal exposure to AEDs and the increased risk of cognitive impairment and ASD was detected at ages of 2 to 6 years.…”
Section: Antiepileptic Drugs (Aeds) As Neurotoxins In Autismmentioning
confidence: 90%
“…In a recent study by Videman et al, carbamazepine, oxcarbazepine, and VPA were associated with impaired early language abilities at the age of 7 months. In contrast, face perception or social attention may be less affected by the neurotoxic effects of the studied AEDs [50]. Previously, the association between prenatal exposure to AEDs and the increased risk of cognitive impairment and ASD was detected at ages of 2 to 6 years.…”
Section: Antiepileptic Drugs (Aeds) As Neurotoxins In Autismmentioning
confidence: 90%
“…An infant with micrognatia, low‐set ears, facial dysmorphism, and unilateral radius aplasia due to lamotrigine and oxcarbazepine exposure during pregnancy was reported . A prospective cohort concluded that in utero exposure to oxcarbazepine was associated with impaired early language abilities at the age of 7 months . A cohort study that included 2600 children exposed to antiepileptics during pregnancy and 771,412 unexposed children showed that oxcarbazepine had a low risk of major congenital malformation (1.8% for oxcarbazepine monotherapy, odds ratio 0.64, p=0.66) .…”
Section: Discussionmentioning
confidence: 99%
“…5 A prospective cohort concluded that in utero exposure to oxcarbazepine was associated with impaired early language abilities at the age of 7 months. 31 A cohort study that included 2600 children exposed to antiepileptics during pregnancy and 771,412 unexposed children showed that oxcarbazepine had a low risk of major congenital malformation (1.8% for oxcarbazepine monotherapy, odds ratio 0.64, p=0.66). 3 Although the use of oxcarbazepine appeared to be relatively safe, further studies are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 111 studies, forty-six (41%) obtained their data from an administrative database/registry ( 116,117,119,120,123,125), and four (4%) studies did not clearly specify the data source (66,(79)(80)(81). Selection of data sources has changed over time with administrative databases/registries comprising large numbers of participants becoming the most commonly used data source in recent years.…”
Section: Types Of Data Sources Usedmentioning
confidence: 99%